Real Time Environmental Monitoring in Palm Oil Plantation Using Wireless Sensor Network - Reza Firsandaya Malik; Muhammad Hafiz; achmad Nopransyah; Muhammad Reyhan Zalbina; Tri Wanda Septian (IAES Indonesia Section, 2015)
The production of the palm oil accounted for 10.15%of total palm oil production in Indonesia. Farmland monitoringsystem is designed to determine the condition of temperature andsoil moisture on oil palm plantation. In this study, we design andbuild a Wireless Sensor Network (WSN) with fitted temperatureand moisture sensors for monitoring soil quality. The process oftemperature and moisture data communication from sensor nodesto the sink using a routing protocol that named Power-EfficientGathering in Sensor Information Systems (PEGASIS). The routingprocess in the PEGASIS is the nodes will form a chain by selectinga leader node as a gateway. The development of WSN is composedof 3 nodes and 1 sink with three different scenarios. The firstscenario is placed moisture sensors on three nodes (single sensor),the second is placed the temperature sensors on three nodes (singlesensor) and the third is placed moisture sensor on two node and onenode equiped by temperature sensor (multi sensor). The evaluationof WSN communication using the PEGASIS routing protocolcompared to the direct transmission using delay, packet loss andenergy have done. The results obtained are the difference betweenthe lifetime sensor nodes between direct transmission and thepegasis is 7 minutes time difference. For the average delay ofPEGASIS and direct transmission is 31.23 and 30.92 msrespectively. All transmission in both scheme have packet loss 0%.Conclusion, the WSN has successfully implemented with longer lifetime energy using PEGASIS than direct transmission methods.